The chemical percolation devolatilization model applied to the devolatilization of coal in high intensity acoustic fields - Veras, CAG; Carvalho, J. A.; Ferreira, M. A. (Soc Brasileira Quimica, 2002)
The chemical percolation devolatilization model (CPD) was extended for the prediction of drying and devolatilization of coal particles in high intensity acoustic fields found in Rijke tube reactors. The acoustic oscillations enhance the heat and mass transfer processes in the fuel bed as well as in the freeboard, above the grate. The results from simulations in a Rijke tube combustor have shown an increase in the rate of water evaporation and thermal degradation of the particles. The devolatilization model, based on chemical percolation, applied in pulsating regime allowed the dynamic prediction on the yields of CO, CO2, CH4, H2O, other light gases as well as tar which are important on ignition and stabilization of flames. The model predicted the quantity and form of nitrogen containing species generated during devolatilization, for which knowledge is strategically indispensable for reducing pollutant emissions (NOx) in flames under acoustic excitation.
Keywords: chemical percolation devolatilization model; acoustic fields; Rijke tube